A Study of Parameters Affecting Atom Probe Tomography Specimen Survivability. (5th November 2018) - Prosa, Ty J.; Strennen, Savanna; Olson, David; Lawrence, Dan; Larson, David J.
Abstract: Specimen survivability is a primary concern to those who utilize atom probe tomography (APT) for materials analysis. The state-of-the-art in understanding survivability might best be described as common-sense application of basic physics principles to describe failure mechanisms. For example, APT samples are placed under near-failure mechanical-stress conditions, so reduction in the force required to initiate field evaporation must provide for higher survivability—a common sense explanation of survivability. However, the interplay of various analytical conditions (or instrumentation) and how they influence survivability (e.g., decreasing the applied evaporation field improves survivability), and which factors have more impact than others has not been studied. In this paper, we report on the systematic analysis of a material composed of a silicon-dioxide layer surrounded on two sides by silicon. In total, 261 specimens were fabricated and analyzed under a variety of conditions to correlate statistically significant survivability trends with analysis conditions and other specimen characteristics. The primary result suggests that, while applied field/force plays an obvious role in survivability for this material, the applied field alone does not predict survivability trends for silicon/silicon-dioxide interfaces. The rate at which ions are extracted from the specimen (both in terms of ions-per-pulse and pulse-frequency) has similar importance.